1998
DOI: 10.1038/sj.onc.1201895
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of AUF1 and HuR, two c-myc mRNA binding proteins

Abstract: Several proteins that may regulate c-myc mRNA posttranscriptionally were previously isolated and characterized. Two of them, HuR and AUF1, bind speci®cally to the 3' untranslated region (UTR) of c-myc mRNA. Because c-myc is regulated post-transcriptionally in various mouse tissues, including quiescent tissues, fetal liver and regenerating liver, we investigated whether HuR and AUF1 expression was also regulated in these tissues. Concerning AUF1, we analysed the expression of various mRNA and protein isoforms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 27 publications
2
56
0
Order By: Relevance
“…It is possible that LFA-1-mediated signals, notably resulting in HuR translocation and consequential RNA stabilization, are more effectively targeted to class II rather than class I sequences. This idea seems unlikely, as HuR has been shown, in fact, to bind the 3Ј-UTR of c-myc RNA (36). Rather, there are multiple cis-elements within the c-myc transcript that are degradation targets and control its half-life, including sequences within the 5Ј-UTR, as well as within exons 2 and 3 (37).…”
Section: Discussionmentioning
confidence: 92%
“…It is possible that LFA-1-mediated signals, notably resulting in HuR translocation and consequential RNA stabilization, are more effectively targeted to class II rather than class I sequences. This idea seems unlikely, as HuR has been shown, in fact, to bind the 3Ј-UTR of c-myc RNA (36). Rather, there are multiple cis-elements within the c-myc transcript that are degradation targets and control its half-life, including sequences within the 5Ј-UTR, as well as within exons 2 and 3 (37).…”
Section: Discussionmentioning
confidence: 92%
“…The signal detected by the AUF1 probe corresponds to RNAs encoding all four isoforms (Lafon et al, 1998). Speci®c signals were detected with each probe as early as E8.5 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…However, the functions of HuR and AUF1 in cell proliferation and dierentiation have yet to be investigated. Although proposed to be ubiquitous, expression of these proteins has been reported only in a small number of experiments performed with dierentiated cells, either from tissue culture (Lo¯in et al, 1999), adult tissues (Ma et al, 1996;Lafon et al, 1998) or tumours (Nabors et al, 1998). Thus our knowledge of their developmental expression remains very limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in cells capable of proliferation such as fetal hepatocytes and adult lymphocytes, where AUF1 levels are much higher compared with adult hepatocytes, it could protect c-myc mRNA from decay (Lafon et al 1998). Current data in transgenic mice showed that overexpression of AUF1 followed by deregulation of c-myc, c-fos, and c-jun led to the development of sarcomas with strong cyclin D1 expression.…”
Section: Introductionmentioning
confidence: 99%